ANALISIS FAKTOR FAKTOR YANG MEMEPENGARUHI PROFITABILITAS PADA PERUSAHAAN CONSUMER CYCLICASLS YANG TERDAFTAR DI BURSA EFEK INDONESIA - Lim, Steven (Fakultas Ekonomi dan Bisnis Universitas Islam DR KH EZ Mutaqien, 2025)
Consumer Cyclicals is a sector that is greatly influenced by changes in the economic cycle. Companies in this sector, such as those engaged in automotive, durable consumer goods, tourism, entertainment, and retail, tend to experience increased demand when economic conditions improve and decline during recessions. The purpose of this study is to analyze the factors that affect profitability in Consumer Cyclicals companies listed on the Indonesia Stock Exchange. This study uses a quantitative approach with the type of associative research. The results of this study show that factors such as leverage, company size, liquidity, and sales growth have a significant influence on the profitability of companies in the Consumer Cyclicals sector listed on the IDX. Low leverage, as seen in PT Ace Hardware Indonesia Tbk (DER 0.5 and ROE 12%), contributed to higher profitability. Company size also plays a role, with large companies such as PT Indomaret (market capitalization of IDR 50 trillion and ROA of 7%) showing better performance. In addition, high liquidity (PT MAP Aktif Adiperkasa Tbk, current ratio of 2.0 and ROE of 11%) and stable sales growth also support the company's profitability. Companies with good governance and cost efficiency, such as PT Ace Hardware Indonesia Tbk, also showed better performance (GCG score of 85 and net profit margin of 8%). Therefore, companies in this sector need to focus on managing their capital structure, liquidity, and innovation to ensure their continuity and profitability growth